2009
DOI: 10.1007/s12199-009-0080-2
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation as a cardiovascular risk factor and pulse wave velocity as a marker of early-stage atherosclerosis in the Japanese population

Abstract: Inflammation and pulse wave velocity (PWV) are a potential risk factor and marker, respectively, for atherosclerosis in the primary prevention setting. Atherosclerosis is now generally accepted to be an inflammatory disorder of the arterial wall, and the high-sensitivity Creactive protein (hs-CRP) level has been reported to be a strong predictor of cardiovascular events. High-sensitivity-CRP is associated with two factors related to inflammation: (1) the local production of CRP by atheromatous tissue or corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 58 publications
1
12
2
Order By: Relevance
“…Model 2 included baPWV categorized by the cutoff value and model 3 included baPWV categorized by quartile distributions with the same adjustment applied. indicates arteriosclerotic change (2)(3)(4)(5)(6)(7)(8)(18)(19)(20)(21)(22)(23)(24)(25)(26). Although hypertension and age were independently associated with WMHs in that cohort (5), these risk factors were not statistically significant in the present study.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Model 2 included baPWV categorized by the cutoff value and model 3 included baPWV categorized by quartile distributions with the same adjustment applied. indicates arteriosclerotic change (2)(3)(4)(5)(6)(7)(8)(18)(19)(20)(21)(22)(23)(24)(25)(26). Although hypertension and age were independently associated with WMHs in that cohort (5), these risk factors were not statistically significant in the present study.…”
Section: Discussioncontrasting
confidence: 50%
“…Matsumoto et al demonstrated that baPWV!18 m/s is the best cutoff value to identify increased CCAIMT in hypertensive patients (7). Furthermore, there is an opinion that a baPWV cutoff value should be 18 m/s, because baPWV is roughly 1.5-fold the magnitude of carotid-femoral pulse wave (cfPWV; conventional measurement of arterial stiffness) (8,20). The cutoff value of cfPWV >12 m/s for total cardiovascular risk is recommended in the Guidelines for the Management of Arterial Hypertension of the European Society of Hypertension and the European Society of Cardiology (17,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum LDL-C, TG, and LDL-C/HDL-C have been used as risk indicators for arteriosclerosis. The serum hs-CRP level is increasingly used in healthy adults [33,34] and children [7][8][9][10][11]35] as a biochemical marker of vascular inflammation associated with atherosclerosis. Yoshida et al reported a cross-sectional analysis of the association of serum hs-CRP and other serum parameters with physique in 568 Japanese children (7-10 years old).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies of diabetic vascular responses clearly demonstrated that blood vessels from patients with diabetes mellitus have reduced nitric oxide bioavailability. [30][31][32] In China, there is a significantly higher prevalence of obesity, diabetes mellitus, dyslipidemia, hypertension, and the metabolic syndrome in people in the north or in urban areas compared with the south or rural areas. 33 In northeastern China, the local cuisines are relatively salty and greasy, with wheat as the staple food due to the dry arctic winter.…”
Section: Effects Of Metabolic Syndrome On Cavimentioning
confidence: 99%